Parental attitudes of children without neurodevelopmental disorders and inclusion of children with Special Educational Needs (SEN) - Campos, Sofia (2022)
Over the last decade there has been a development on the inclusion of students with Special Educational Needs (SEN) in mainstream education. The general objective is to analyze the attitudes of parents of children without neurodevelopmental disorders regarding the inclusion of children with Special Educational Needs. Methods: This is a comparative and correlational study and aims to: Characterize and analyze the possible differences in attitudes of parents of children without neurodevelopmental disorders regarding the inclusion of children with SEN considering the three disorders. The results revealed that parents of children without neurodevelopmental disorders tend to show positive attitudes towards the inclusion of children with SEN. It was found that the type of disturbance and the description that is made of children with SEN have an influence on parental attitudes, which show more positive attitudes towards Hearing Impairment, followed by Trisomy 21, and Behavioral Disorder. Conclusions: Sensitizing parents of children without neurodevelopmental disorders plays an essential role in the messages they convey to their children promoting inclusion.